Comparative Genomics and Phylogenomics of East Asian Tulips (Amana, Liliaceae) - Li, Pan; Lu, Rui-Sen; Xu, Wu-Qin; Ohi-Toma, Tetsuo; Cai, Min-Qi; Qiu, Ying-Xiong; Cameron, Kenneth M.; Fu, Cheng-Xin (Frontiers in Plant Science, 2017)
The genus Amana Honda (Liliaceae), when it is treated as separate from Tulipa, comprises six perennial herbaceous species that are restricted to China, Japan and the Korean Peninsula. Although all six Amana species have important medicinal and horticultural uses, studies focused on species identification and molecular phylogenetics are few. Here we report the nucleotide sequences of six complete Amana chloroplast (cp) genomes. The cp genomes of Amana range from 150,613 bp to 151,136 bp in length, all including a pair of inverted repeats (25,629–25,859 bp) separated by the large single-copy (81,482–82,218 bp) and small single-copy (17,366–17,465 bp) regions. Each cp genome equivalently contains 112 unique genes consisting of 30 transfer RNA genes, four ribosomal RNA genes, and 78 protein coding genes. Gene content, gene order, AT content, and IR/SC boundary structure are nearly identical among all Amana cp genomes. However, the relative contraction and expansion of the IR/SC borders among the six Amana cp genomes results in length variation among them. Simple sequence repeat (SSR) analyses of these Amana cp genomes indicate that the richest SSRs are A/T mononucleotides. The number of repeats among the six Amana species varies from 54 (A. anhuiensis) to 69 (A. kuocangshanica) with palindromic (28–35) and forward repeats (23–30) as the most common types. Phylogenomic analyses based on these complete cp genomes and 74 common protein-coding genes strongly support the monophyly of the genus, and a sister relationship between Amana and Erythronium, rather than a shared common ancestor with Tulipa. Nine DNA markers (rps15–ycf1, accD–psaI, petA–psbJ, rpl32–trnL, atpH–atpI, petD–rpoA, trnS–trnG, psbM–trnD and ycf4–cemA) with number of variable sites greater than 0.9% were identified, and these may be useful for future population genetic and phylogeographic studies of Amana species.